Of myths and markets: how marketisation of the care home sector contributes to circumstances where abuse is more likely to occur and continue. Issue 5 (21st October 2020) - Moore, Steve
Abstract : Purpose: Strategic socio-political views are notably scarce among contemporary discourses on the causes of abuse of vulnerable older people in care and nursing homes. This paper aims to catalyse higher order consideration and discussion of one socio-political characteristic that has relevance to the issue of abuse, that is, the market-like environment in which care and nursing homes in England operate. In doing so, the paper argues that the now firmly established but imbalanced "quasi-market" of care that has developed over many years fosters conditions under which both poor care and abuse are more likely to occur. The evidence presented in the paper focusses primarily on the rise to dominance of for-profit care home provision and the contraction of public sector provision. The paper does not examine in detail the characteristics and market presence of the not-for-profit sector because it has not held a numerically significant market share either historically or contemporarily. Design/methodology/approach: Outcomes of the marketisation of the care home sector that has its origins in the political landscape prevailing in 1979 and thereafter, along with the concurrent development of its regulation and oversight, are narrated and analysed. From this, a mythos of the motives behind the transition to a market-like economy that has taken place over four decades is developed and used to explain how prevailing market conditions contribute to the perpetuation of poor care and abuse. Findings: In the opinion of the author, there are identifiable consequences arising from the evolution of the current care economy that dispel the beliefs that providing care by means of current market-like arrangements is advantageous, that the independent regulation and monitoring of such a market is unproblematic and effective, and that the "consumers" in this market are exercising personal choice, in accord with classical economic theory. Practical implications: The paper offers the opportunity for the reader to consider how the development of a "quasi" market of care and nursing home services that has come to be dominated by for-profit private providers, and that is subject to ineffective oversight, may have contributed to conditions where abuse is more likely to occur and endure. Originality/value: This is a conceptual paper that explores the consequences of the creation of the market-like economy of care in which care and nursing homes now operate and suggests that it is time for prevailing market conditions to be re-visited and subjected to remedial strategic intervention.